Capital markets : African and global - Osaze, Bob Esosa (Lagos, Nigeria : The Bookhouse Company, 2007)
Takes a look at the features, characteristics and problems of capital markets in Africa with Nigeria as a case study. It also focuses on the factors that inhibit foreign capital inflow, foreign investor interest and general underdevelopment of the long end of the financial system in Africa.
Includes bibliographical references (p. 409-416).
oif 10/08/15
Loan
Keywords: Capital market; Securities